Community Participation in Covid-19 Prevention and Transmission - Ganjar UngguL Pamenang; Prihanto Prihanto (Jurnal Kesehatan, 2022)
Community participation in Covid-19 prevention and transmission is very important, because the community is not only the object but also the subject in handling Covid-19. Community participation can provide benefits in preventing and handling Covid-19; it will reduce morbidity and mortality in the area. The purpose of this literature review is to know the role of the community in Covid-19 prevention and transmission. The method used is literature review. Community participation in Covid-19 prevention and transmission is not only the responsibility of each individual or health worker but it is the responsibility of the entire community. Community participation that is carried out actively and participatively will make of the success of the programs that are being carried out become higher and maximally. The community is not only an object but also a subject in every program or activity that is being carried out. Efforts are being made to increase community participation, namely through socialization, counseling or health education and discussions. These activities will provide knowledge and insight for the community, and the main point is that it will raise public awareness to be actively involved and take part in the success of activities that are being carried out for the common interest, creating a healthy community, avoiding the spread and transmission of Covid-19.